Operational logistics the art and science of sustaining military operations - Kress, Moshe (Management for professionals, 2016)
This book explores the theoretical foundations and applications of military operational logistics (OpLog). OpLog theory has two facets: qualitative and quantitative.The qualitative facet is imbedded in the theory of operational level of war or operational art. It includes principles, imperatives and tenets, which are stated and analyzed in the first few chapters. The quantitative facet relates to the scientific aspects of OpLog. It is manifested by formal network models representing structural and operational features of an OpLog system. The book examines the two facets and integrates them into a unified presentation.